Coprecipitation for the Determination of Copper(II), Zinc(II), and Lead(II) in Seawater by Flame Atomic Absorption Spectrometry - AYDIN URUCU, OYA (TAYLOR & FRANCIS INC, 2015)
A TiO(OH)(2) precipitate was used for the preconcentration of copper(II), zinc(II), and lead(II) in seawater prior to determination by flame atomic absorption spectrometry. The influence of pH, sample volume, amount of precipitate, and centrifugation time were optimized for quantitative recoveries of the analytes. Under the optimum conditions, the detection limits of copper(II), lead(II), and zinc(II) were 4.3, 9.7, and 9.6 micrograms per liter, respectively. The recoveries of analytes were between 95.00 and 103.00 percent with the relative standard deviation below 6 percent. The procedure was validated by the analysis of NASS-5 and SPS-WW1 Batch 109 standard reference materials and the procedure was successfully applied to seawater.
Keywords: Flame atomic absorption; Zinc; Copper; Lead; Seawater; TRACE-ELEMENTS; WATER SAMPLES; SELECTIVE DETERMINATION; METAL IONS; PRECONCENTRATION; SEPARATION; HYDROXIDE; EXTRACTION